2001
DOI: 10.1152/jappl.2001.91.3.1073
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of muscle GLUT-4 transcription by AMP-activated protein kinase

Abstract: Skeletal muscle GLUT-4 transcription in response to treatment with 5-aminoimidazole-4-carboxamide-1-beta-D-ribofuranoside (AICAR), a known activator of AMP-activated protein kinase (AMPK), was studied in rats and mice. The increase in GLUT-4 mRNA levels in response to a single subcutaneous injection of AICAR, peaked at 13 h in white and red quadriceps muscles but not in the soleus muscle. The mRNA level of chloramphenicol acyltransferase reporter gene which is driven by 1,154 or 895 bp of the human GLUT-4 prox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
187
2
10

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(208 citation statements)
references
References 51 publications
9
187
2
10
Order By: Relevance
“…Since regulation of glucose uptake is critical for treatment of the metabolic syndrome as well as diabetes, upregulation of GLUT4 at the protein and gene level is an important mechanism in the enhancement of glucose uptake in animal cells. It has been reported that AMPK controlled the capacity of skeletal muscle carbohydrate metabolism by regulating the abundance of GLUT4, which increased the maximal rate of glucose transport into skeletal muscle [36,37]. Eid et al have shown that quercetin and quercetin glycosides stimulated AMPK and enhanced basal glucose uptake in C2C12 cells Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Since regulation of glucose uptake is critical for treatment of the metabolic syndrome as well as diabetes, upregulation of GLUT4 at the protein and gene level is an important mechanism in the enhancement of glucose uptake in animal cells. It has been reported that AMPK controlled the capacity of skeletal muscle carbohydrate metabolism by regulating the abundance of GLUT4, which increased the maximal rate of glucose transport into skeletal muscle [36,37]. Eid et al have shown that quercetin and quercetin glycosides stimulated AMPK and enhanced basal glucose uptake in C2C12 cells Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have reported that AICAR treatment increased muscle GLUT4 mRNA and protein in a fiber type-specific manner (Buhl et al, 2001;Zheng et al, 2001). First, we confirmed the effect of AICAR on GLUT4 mRNA level as a positive control.…”
Section: Effects Of Aicar Injection On Mct4 Expression In Rat Skeletamentioning
confidence: 99%
“…Several studies have shown that 5-aminoimidazole-4-carboxamide-1-ÎČ-D-ribofuranoside (AICAR), an AMPK activator, activates glucose transport and increases the expression of glucose transporter 4 (GLUT4) and several metabolic enzymes in skeletal muscle (Buhl et al, 2001;Holmes et al, 1999Holmes et al, , 2005Ojuka et al, 2002;Stoppani et al, 2002;Winder et al, 2000;Zheng et al, 2001). It has been reported that an increase in glucose uptake induced by AICAR results in increased lactic acid production in isolated rat skeletal muscle (Miyamoto et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Coimmunoprecipitation and transient transfection assays demonstrated that GEF and MEF2A exert synergistic activation of the GLUT4 gene promoter by interacting with each other. Moreover, activation through these two regulatory cis-elements was affected by AMPK (56). Regulation of GEF by AMPK may be stimulated both by upregulation and accompanying phosphorylation.…”
Section: Muscle-specific Glut4 Enhancer Factor (Gef)mentioning
confidence: 99%